Key insights from studies on the stability of personality disorders in different age groups - d’Huart, Delfine; Seker, Süheyla; Bürgin, David; Birkhölzer, Marc; Boonmann, Cyril; Schmid, Marc; Schmeck, Klaus; Bach, Bo (Frontiers in Psychiatry, 2023)
While for decades, temporal stability has been conceived as a defining feature of personality disorders (PDs), cumulative findings appear to question the stability of PDs and PD symptoms over time. However, stability itself is a complex notion and findings are highly heterogenous. Building upon a literature search from a systematic review and meta-analysis, this narrative review aims to capture key findings in order to provide critical implications, both for clinical practice and future research. Taken together, this narrative review revealed that unlike previous assumptions, stability estimates in adolescence are comparable to stability estimates in adulthood and PDs and PD symptoms are not that stable. The extent of stability itself depends yet on various conceptual, methodological, environmental, and genetic factors. While findings were thus highly heterogenous, they all seem to converge in a notable trend towards symptomatic remission, except for high-risk-samples. This challenges the current understanding of PDs in terms of disorders and symptoms and argues instead in favor of the AMPD and ICD-11 reintroducing the idea of self and interpersonal functioning as the core feature of PDs.